AB0195 Proteomic approach identifies differential protein expression in cultured fibroblasts under stimulation with tgf-Β1. (12th June 2018) - Vivier, S.; Chepy, A.; Bray, F.; Guerrier, T.; Balden, M.; Rolando, C.; Hachulla, E.; Launay, D.; Dubucquoi, S.; Sobanski, V.
Abstract : Background: Fibroblasts (Fb) are key effectors cells in systemic sclerosis (SSc). 1 Fb stimulation with TGF-β1 is usually considered as the positive control in studies assessing the fibrogenesis in SSc. 2 Yet, the lack of standardisation of TGF-β1 stimulation might be responsible for discrepancies in experiments performed in different conditions. Proteomic approach allows the analysis of differential expression of the whole proteins (proteome) in Fb, and appears an interesting approach to compare different culture conditions. Objectives: We designed this study to compare the whole protein expression in Fb stimulated by TGF-β1 in different conditions. Methods: At fifth passage, primary culture of human Fb from healthy subjects (ATCC; PCS-201–012) were stimulated or not with different concentrations of recombinant human active TGF-β1 (0.04, 1, and 5 ng/mL) (R and D Systems; 240-B-002) during 24, 48 and 72 hours. Proteins were extracted and analysed using an eFASP LC-MS/MS approach on an Orbitrap mass spectrometer (Thermo Scientific; Q Exactive +). Proteins quantitation was performed by Maxquant and statistical analysis by Perseus using ANOVA and principal component analysis (PCA). Results: A total of 3267 proteins were identified, of which 1957 showed differential expression using ANOVA analysis. PCA revealed several clusters of differential proteins expression (figure 1). There were clear clusters of protein expression related to (i) unstimulated and stimulated conditions, (ii) between the three different times of stimulation and (iii) to TGF-β1 concentrations used. Although the expression of proteins in Fb exposed to 0.04 and 1 ng/mL of TGF-β1 during 72 hour were rather close, there was a unique proteins profile related to the condition with 5 ng/mL of TGF-β1 during 72 hour. Figure 1: PCA representation of differential proteins expression in different conditions. [TGF-β1]=0.04 ng/mL: square; [TGF-β1]=1 ng/mL: circle; [TGF-β1]=5 ng/mL: diamond. The more the points appear distanced, the more different is the protein expression. Conclusions: This study highlights a variation of proteins expression depending on both stimulation time and TGF-β1 concentrations in Fb culture. The identification of protein differentially expressed will provide insights in the impact of TGF-β1 on Fb physiology under stimulation conditions. These data underline the need of standardisation of culture conditions to allow inter-data comparisons using in sensitive "omic" approaches. References: [1] Garret SM, Frost DB, Feghali-Bostwick C. The mighty fibroblast and its utility in scleroderma research. J Scleroderma Relat Disord2017;2(2):69–134. [2] Verrecchia F, Mauviel A. Transforming growth factor-beta signaling through the Smad pathway: role in extracellular matrix gene expression and regulation. J Invest Dermatol2002Feb;118(2):211–5. Disclosure of Interest: None declared